Confiabilidade teste-reteste de um protocolo de coleta do sinal eletromiográfico do músculo masseter em indivíduos com disfunção temporomandibular - Nakamura, Cindy Mozer (2022)
Introduction: Temporomandibular disorder (TMD) is a common painful condition on the temporomandibular joint and associated muscles that can affect from 11% to 34%. Therefore, it is important to determine the variation in electromyography (EMG) measurements before proposing an EMG signal recording protocol to assess the effectiveness of therapies administered to improve masticatory muscle function in this population. Objectives: To verify the test-retest reliability of a protocol for collecting the electromyographic signal from the masseter muscle in TMD patients. Methods:A cross-sectional study comprising 20 individuals with TMD aged between 18 and 50 years. The EMG signal of the masseter muscle was collected in two test sessions (test and retest) with an interval of 7 days between collections in two conditions: maximum habitual intercuspation (MIH) and Isotonia (ISOT-chewing). For each test condition, 3 recordings of the EMG signal were performed, which was evaluated by the variables integral (iEMG) and the root mean square of the signal (RMS). Relative and absolute reliability were evaluated using the intraclass correlation coefficient (ICC2,k and ICC2,1) and the measurement standard error (SEM) respectively. Results: Intraday analysis, the ICC was considered excellent for the values verified by the RMS variables (ICC= 0.85 to 0.96) and iEMG (ICC= 0.85 to 0.95) in both muscles, with the first test session (test) presenting a greater interval of SEM (SEM=3.09 to 7.59) in relation to the second test session (retest) (SEM=3.64 to 6.77). Regarding the interday reliability in both test conditions (MHI and ISOT), the ICCs revealed poor reliability for the variables RMS (ICC2.1= 0.03 to 0.29) and iEMG (ICC2.1= 0.08 to 0.39) being the SEM considered high for these measures (SEM= 11.98 to 17.65). Conclusions: The protocol for collecting the EMG signal from the masseter muscle in individuals with TMD demonstrated that the data are reproducible only in the same collection session, while for collections on alternate days, the reliability was poor.